Enhancement Effect of BAP and Spent Mushroom Compost in Micro-Propagation of Sabah Snake Grass - Wan Nurul Hidayah, Wan Anuar; Tan, Suat Hian; Siti Hamidah Radiyah, Shiekh Mahmud; Wan Nurhafisya, Mior Norazmi; Engku Fatimah Syairah, Engku Safruddin (Science Publication, 2019)
Medicinal plants which is Clinacantus nutans (C. nutans) that known as Sabah Snake Grass or Belalai Gajah can treat several diseases including cancer. In order to provide and grow this plant in large number for health and pharmaceutical industry, one of the solutions is through the plant tissue culture technique. In this experiment, C. nutans was cultured under controlled conditions which to provide sterile plantlets. The surface sterilization using three methods which involved ethanol, Clorox and mercuric chloride. In the comparison of them, it was found that the use of 70% ethanol (5 min) followed by 30% clorox (5 min) then with 0.1% mercuric chloride for one hour was the most effective sterilization method which gave the highest survival rate (100%) and zero contamination rate. The sterile explants were then cultured in media containing different concentrations of Benzylaminopurine (BAP) and Pleurotus ostreatus Spent Mushroom Compost (SMC). The SMC was tested and compared in powder and extracted form. The observations were made every week on responds of the culture using variables which are number of shoots, length of shoots and number of leaves. This article was aimed to evaluate the enhancement effect of BAP and SMC in micro-propagation of Sabah Snake Grass. The authors found that the best concentration for BAP is 1.0 µM. It produced 3.5±0.926 number of shoots and 2 µM BAP produced 7.286±1.496 number of leaves in their findings. When BAP and SMC were tested in combination, they managed to produce high number of shoots and leaves. Their result revealed a number of shoots (5.750±0.500) produced by 2% extract of SMC and some leaves (11.890±1.965) by 8% extract of SMC when both were cultured together with 1.0 µM BAP respectively. The authors thought that there was enhancement effect on the combination of BAP with extracts of SMC which gave about double regeneration rate as compared with the BAP alone and this method had high potential for future research in producing mass propagation of C. nutan and other related study by reducing the usage of plant growth regulator which may reduce the cost of micro-propagation of tissue culture plants.